2018
DOI: 10.3390/toxins10100391
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Toxicities of Radix Aconiti Lateralis Preparata (Fuzi) and the Toxicokinetics of Its Main Diester-Diterpenoid Alkaloids

Abstract: The processed lateral root of Aconitum carmichaelii Deb (Aconiti Radix lateralis praeparata or Fuzi) is a potent traditional herbal medicine extensively used in treatment of cardiovascular diseases, rheumatism arthritis, and bronchitis in many Asian countries. Although Fuzi has promising therapeutic effects, its toxicities are frequently observed. Three main C19-diester-diterpenoid alkaloids (DDAs) are believed to be the principal toxins of the herb. Although toxicokinetic profiles of the toxic DDAs have alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…There are many studies on the analgesic effect of mesaconitine. Their relationship of efficacy‐dosage and pharmacokinetic studies has been reported . However, the detailed analgesic mechanism of MA needs further clarification.…”
Section: Neuropharmacological Effect Of Aconiti Lateralis Radix Praepmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies on the analgesic effect of mesaconitine. Their relationship of efficacy‐dosage and pharmacokinetic studies has been reported . However, the detailed analgesic mechanism of MA needs further clarification.…”
Section: Neuropharmacological Effect Of Aconiti Lateralis Radix Praepmentioning
confidence: 99%
“…They are highly efficient, stable and durable . Moreover, metabolomics has been frequently used to examine Fuzi's toxicity and pharmacological mechanisms . This approach can be used to distinguish Aconitum carmichaelii and identify compounds that have development potential .…”
Section: Toxicity and Precautionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a comprehensive MA metabolism database still needs to be built for future pharmacological studies and clinical use [80]. In order to better understand the toxicity of MA, other advanced methods like an electrocardiogram, histopathology, serum biomarkers, and lipidomic profile changes need to be applied [79].…”
Section: Side Effects Of Mamentioning
confidence: 99%
“…Many common drugs in the Chinese materia medica are known to be toxic, causing damage to nervous, liver, renal, respiratory system, and reproductive system (Table 3) (6)(7)(8)(9)(10)(11)(12)(13)(14). The toxic components from TCM herbs include alkaloids, anthraquinones, aristolochic acids, cardiac glycosides and others (15).…”
Section: How To Reduce the Toxicity Of Tcms?mentioning
confidence: 99%